Correlation of Degree of Carrying Angle with Dominent Arm of Medical Students - Rehman, Zainab; iftikhar, Shazia; Waheed, Nazish; Naz, Falak; Sultana, Shagufta; Shaukat, Sadia (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Objective The objective of this study was to obtain gender-specific data in variations of carrying angle on full extension of the elbow and its correlation with the dominant arm. Methodology One hundred and eighty healthy volunteers participated in the study with an equal number of males (n=90) and females (n=90). The average age of both ranged from 18 to 22 years. All individuals with normal and healthy architecture with no history of arm or forearm fracture or surgery involving the elbow, no history of neural defects, or congenital variance were included in the study. Carrying angles of elbows of both dominant and non-dominant sides were measured in the case of each volunteer with the help of a Goniometer. Results The results showed that the carrying angle was found to be greater in females (14.75±1.2) as compared to males (12.96±1.4). Also, the dominant arm of both males and females displayed an increased value of carrying angle than the non-dominant one which was statistically significant (p=.001) Conclusion Hence in this study, it was found the carrying angle at the elbow is greater in females and is associated significantly with the dominance of the arm. Key words: Carrying angle, Goniometer, Dominant and Non-dominant arm